Development of Digital-Based Indonesian Language Teaching Materials to Enhance Language Skills - Muh. Safar (PT. Anagata Sembagi Education, 2026)
The rapid digital transformation in education requires innovative Indonesian language teaching materials that are interactive, skill-oriented, and aligned with students’ digital learning habits. However, many existing materials remain text-based and insufficiently integrated with multimedia and contextual approaches. This study aimed to develop and evaluate digital-based Indonesian language teaching materials to enhance students’ language skills. The research employed a Research and Development (R&D) design using the ADDIE model, including needs analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation sheets, student response questionnaires, observations, and pretest–posttest assessments measuring reading, writing, and speaking skills. The results indicated that the developed materials achieved a “very valid” category from experts (mean score 4.45; 88.9%). Statistical analysis showed significant improvement in students’ language skills after implementation (p < 0.001), with notable gains in reading, writing, and speaking performance. These findings demonstrate that digital-based teaching materials designed with interactive multimedia, contextual tasks, and cultural integration effectively enhance language competence. In conclusion, structured digital instructional design can serve as an evidence-based model for improving Indonesian language learning in primary education.